MSC therapy ameliorates experimental gouty arthritis hinting an early COX-2 induction - Medina, Juan Pablo; Bermejo-Álvarez, Ismael; Pérez-Baos, Sandra; Yáñez, Rosa; Fernández-García, María; García-Olmo, Damián; Mediero, Aránzazu; Herrero-Beaumont, Gabriel; Largo, Raquel (Frontiers in Immunology, 2023)
Objective The specific effect of Adipose-Derived Mesenchymal Stem Cells (Ad-MSC) on acute joint inflammation, where the response mostly depends on innate immunity activation, remains elusive. The pathogenesis of gouty arthritis, characterized by the deposition of monosodium urate (MSU) crystals in the joints, associated to acute flares, has been associated to NLRP3 inflammasome activation and subsequent amplification of the inflammatory response. Our aim was to study the effect of human Ad-MSC administration in the clinical inflammatory response of rabbits after MSU injection, and the molecular mechanisms involved. Methods Ad-MSC were administered by intraarterial route shortly after intraarticular MSU crystal injections. Joint and systemic inflammation was sequentially studied, and the mechanisms involved in NLRP3 inflammasome activation, and the synthesis of inflammatory mediators were assessed in the synovial membranes 72h after insult. Ad-MSC and THP-1-derived macrophages stimulated with MSU were co-cultured in transwell system. Results A single systemic dose of Ad-MSC accelerated the resolution of local and systemic inflammatory response. In the synovial membrane, Ad-MSC promoted alternatively M2 macrophage presence, inhibiting NLRP3 inflammasome and inducing the production of anti-inflammatory cytokines, such as IL-10 or TGF-β, and decreasing nuclear factor-κB activity. Ad-MSC induced a net anti-inflammatory balance in MSU-stimulated THP-1 cells, with a higher increase in IL-10 and IDO expression than that observed for IL-1β and TNF. Conclusion Our in vivo and in vitro results showed that a single systemic dose of Ad-MSC decrease the intensity and duration of the inflammatory response by an early local COX-2 upregulation and PGE2 release. Ad-MSCs suppressed NF-kB activity, NLRP3 inflammasome, and promoted the presence of M2 alternative macrophages in the synovium. Therefore, this therapeutic approach could be considered as a pharmacological alternative in patients with comorbidities that preclude conventional treatment.